Recent Advances in the Application of MOFs in Supercapacitors - Christos Argirusis; Maria-Eleni Katsanou; Niyaz Alizadeh; Nikolaos Argirusis; Georgia Sourkouni (Batteries)
As the need for energy is constantly increasing and in the long term fossil fuels are not an option because of global overheating due to the greenhouse effect, alternative energy production concepts such as photovoltaics, wind energy, IR energy harvesters etc., have been developed. The problem is that renewable energy sources are stochastic, and therefore there is a need for electrical energy storage either in rechargeable batteries or in high-performance supercapacitors. In this respect, novel materials are needed to meet the challenges that are related to these technologies. Metal–organic frameworks (MOFs) represent highly promising materials for energy storage applications in supercapacitors (SCs) and thus in recent years have become essential for clean and efficient energy conversion and storage. Metal–organic frameworks (MOFs) present numerous benefits as electrocatalysts, electrolyte membranes, and fuel storage materials; they exhibit exceptional design versatility, extensive surface-to-volume ratios, and permit functionalization with multivalent ligands and metal centers. Here we present an overview of MOF-based materials for electrical energy storage using high-performance supercapacitors. This review deals with recent advances in MOF-based materials for supercapacitors. Finally, an outlook on the future use and restrictions of MOFs in electrochemical applications, with focus on supercapacitors, is given.